SECRETS OF JAPANESE EDUCATION - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
The article discusses the Japanese education system, pedagogical skills in schools and preschools, and the achievements of the Japanese education system.